THOR®115 pipes in refinery furnaces. (2nd November 2022) - Locatelli, R.; Coppola, T.; Di Vito, L.; Escorza, E.; Ferrara, A.; Lombardo, P.; Monteleone, N.
Summary: Crude fired heater furnaces in refineries are adopting P5 and P9 steel grades, depending on temperature and feed characteristics. Process conditions, however, are characterised by temperatures up to 600°C, well above the conventional creep threshold, which eventually cause a considerable over-tempering of the material. At the same time, crudes being processed have become more'critical' in terms of sulphur content and TAN (total acid number). THOR®115 steel grade designed by Tenaris already showed very good corrosion resistance against oxidation and sulphidation. In the present work, THOR®115 and P9 have been analysed and compared, considering their static and creep resistance, together with oxidation and corrosion rate occurring on the external and internal surfaces. The output of the benchmark, resulting in a better performance of THOR®115 rather than P9, has been used to develop an economical comparison between the two materials and quantify the advantage to adopt THOR®115 in furnace applications.